Synthesis of nano materials on the base of rice husk ash and CeO2 for application as a growth stimulant for bell peeppers plan (capsicum annuum L.) - Huỳnh , Xuân Trường; Nguyễn, Viết Trung; Nguyễn, Thúy Nhi; Phạm, Trần Thanh Ngân; Đặng , Thị Diệu Linh; Lê Thị, Thu Hương; Cao, Văn Hoàng (Hue University Journal of Science: Natural Science, 2024)
In this study, CeO2/SiO2 material was synthesized and applied as a growth stimulant for bell pepper plants from Ce(NO3)4 precursor and rice husk ash using gamma irradiation method. Material morphology and structure were confirmed through physicochemical characterization methods including: XRD, EDX, IR and SEM characterization. The results of surveying the effects of CeO2/SiO2 materials on the growth and development of bell pepper plants show that CeO2/SiO2 significantly affects the growth and development of bell pepper plants. Experimental data obtained showed that bell pepper yield increased by 22 tons/ha, average root length increased by 3.6 cm and harvest time was 11 days less than the control sample. In addition, bell pepper plants supplemented with CeO2/SiO2 are stronger and do not have yellow leaves. This shows that CeO2/SiO2 has a growth stimulating effect on bell pepper plants.